Knowledge, Attitude, and Practice of Antibiotic Use and Its Resistance among Undergraduate Students at the University of Science and Technology, Sana'a, Yemen - Battah, Mohammed; Halboup, Abdulsalam; Othman, Gamil; Mansoure, Ahmed A.; Syed Sulaiman, Syed Azhar; Ali, Faisal; Al-Khazzan, Abdulrazzaq Y.; Ibrahim, Mohamed Izham Mohamed (Hunan University, 2021)
As a global public health problem, antibiotic resistance is a marker of misuse and overuse of antibiotics worldwide. The widespread use of such medications has been the primary reason for the evolution of antibiotic-resistant pathogens. This study, therefore, aims to assess the knowledge, attitude, and practice (KAP) among medical (MS) and non-medical students (NMS) towards antibiotic use in Sanaa city, Yemen. A descriptive cross-sectional study was conducted amongst 405 undergraduate students, 237 MS and 168 NMS, from February to July 2019 from the University of Science and Technology in Sanaa city, Yemen. Participants (N =405) completed a self-administered questionnaire. Descriptive statistical analysis was performed by MS and NMS to determine their knowledge, attitude, and practice on antibiotics use and resistance. Polytomous logistic regression technique was used to analyze the relationship between selected predictors and good knowledge, practice about the antibiotics. The Alpha level used was 0.05. The majority of students (n = 262, 64.7%) had a good knowledge of antibiotic resistance, while 66.4% (n = 269) of respondents have used antibiotics without prescriptions. A better attitude was noticed among MS compared to NMS. The findings demonstrated that overall, MS scored remarkably better knowledge and practice than NMS towards antibiotic use, respectively {odds ratio (OR) = 18.33 (p < 0.001), 95% confidence level (CL) 2.57 (p < 0.001*) 95% (CL)}. The self-medication rate was quite high, and more than 60% of students were found to consume antibiotics without the physicians prescription. Multivariate regression analysis did not show any significant association between self-medication and gender, the level of practice about antibiotics uses. Students of medical colleges have better KAP demonstrating the importance of curriculum and training in knowledge promotion. The inadequate knowledge about the risk and development of antibiotic resistance reflects the need to grow the students awareness through adequate educational programs regarding proper antibiotic usage.